Operational Considerations for Space Fission Power and Propulsion Platforms. (3rd June 2021) - Klein, Andrew C.; Camp, Allen; McClure, Patrick; Voss, Susan; Borenstein, Elan; VanDamme, Paul
Abstract: As consideration of launching fission reactors into space moves ahead, it is important to consider the issues related to the operation of various types of space nuclear power and propulsion applications. This technical note discusses some of these factors, including possible human and equipment radiation exposures that might occur during different types of missions and the operational stages within those missions, managing the approach to and working around space reactors, maintaining reactors for long-duration operations, controlling reactors and monitoring their availability and health, evaluating possible reactor accident scenarios, planning for planetary protection due to their operation, and post operation decommissioning and disposal. It also includes a number of suggested guidelines for mission and reactor designers to consider as these important utilizations of nuclear power move forward.